Evaluation and analysis of strength values assessed pre and post pitch session in an MLS team during the season and after the off season - Martin Lara-Desales; Enrique Agustín Martínez-Ruiz; Sean Edmond-Buckley; Martín Barcala Furelos; Carlos Lago-Fuentes (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background: In recent decades, sport science has advanced significantly, but injuries in football have also increased, possibly due to increased competitive demands. The reasons behind injuries are complex, involving both external and internal factors. It is crucial to focus on modifiable factors such as training load, physical capabilities, flexibility, and strength. It is also essential to perform specific assessments based on physical needs and the most injured muscle groups in each sport. Therefore, the aim of this study was to (1) determine strength and power values ​​in a Major League Soccer (MLS) professional football team during one season, (2) analyze the results of pre- and post-session assessments, and (3) determine the effect of the transition period on strength and power. Methods: The study included 22 professional football players aged 26.3 ± 3.9 years from a Major League Soccer (MLS) team excluding goalkeepers. Six assessments were performed, of which 3 were pre-throwing session and 3 were post-throwing session, evaluating eccentric hamstring strength using the Nordic hamstring curl with the NordBord system, maximal isometric hip adduction and abduction strength using the ForceFrame, and lower limb power with the countermovement vertical jump (CMJ) on ForceDecks force platforms. Results: Strength and power values ​​established with pre-session assessments show a CMJ height of 43.96 ± 3.92cm, in Nordic hamstring curl 382.46 ± 67.79N (L) and 370.66 ± 65.84N (R), in hip adduction 414.79 ± 73.86N (L) and 424.02 ± 71.88N (R), and in hip abduction 411.93 ± 60.19N (L) and 420.77 ± 60.54N (R). The results showed a significant decrease (P > 0.05) in the Nordic hamstring curl and both hip adduction and abduction in the post-session assessments compared to the pre-session assessments, the CMJ height did not show a significant change (p = ˃0.05). In the pre-season assessment compared to the data obtained in the pre-session assessments a significant decrease in CMJ height was found (p = ˂0.05), while the Nordic hamstring curl and both hip adduction and abduction did not show a significant decrease (p = ˃0.05). Conclusions: The data studied show lower strength values ​​after the session, except for power expressed in CMJ height. After the transition period, hamstring and hip strength (ABD-ADD) did not show significant changes, but CMJ height did. It is suggested to perform strength assessments and strength training prior to the on-field soccer session to obtain accurate baseline profiles and maximize strength and power training adaptations, avoiding biases generated by fatigue. It is also recommended to implement training programs during the transition period to counteract the effects of detraining.